IMPLEMENTASI PENGENDALIAN LAMPU OTOMATIS BERBASIS ARDUINO MENGGUNAKAN METODE FUZZY LOGIC - Akim Manaor Hara Pardede; Novriyenni Novriyenni; Sutris Efendi (TECHSI - Jurnal Teknik Informatika, 2017)
The habit of people in General who often forget to turn off the lights or even accidentally turn it on constantly. This could result in waste of electrical energy. Thereforerequired a tool to turn on the light automatically. However in general are constant lights a flame that is life and death. The level of brightness of lights arranged as needed based on the conditions of light intensity diruangan. One way to detect light intensity sensor is LDR (Light Dependent Resistor). Sensor LDR (Light Dependent Resistor) serves to detect light intensity. Sensor LDR(Light Dependent Resistor) will yield a value that will be processed by the mikrokontroller with the method of fuzzy logic as decision makers. Determination of the level of brightness of light based on fuzzy logic. Fuzzy logic will manipulate the intensityof light in the detection sensors as the decision makers of light output. Based on the design and the results of testing of the devices using the fuzzy method can maximize the performance of a system, as it will work in times of need. Electric energy consumption by implementing a device that has been realized more efficient compared to a regular light.